Properties of Analysts' Forecasts for Romanian Listed Companies: How Much Do Firm-Specific Factors Matter? - Mihaela Ionascu (Journal of Accounting and Management Information Systems (JAMIS), 2011)
This paper seeks to explore the properties of analysts' forecast accuracy for companies listed on Bucharest Stock Exchange (BSE). Based on a sample of 266 firm-month observations (predictions made in 2008 for 2009 and 2010), the paper investigates several firm-specific factors documented by the literature to have a significant impact on forecast accuracy, and shows that for Romanian listed companies, forecast errors for earnings per share reported under local GAAP are negatively correlated with the size of the firm and the corporate governance policies. The results are convergent with those documented in international contexts, showing that larger firms as well as those which are better governed are more likely to provide additional disclosures, and thus increase forecast accuracy.
Keywords: M41; G17; G10; 650; Properties of analysts' forecast; corporate governance; information environment